Symbols and labels in war reporting: a study on the nature of prejudice from the perspectives of general semantics / Mohd Rajib Ab. Ghani and Faridah Ibrahim - Ab. Ghani, Mohd Rajib; Ibrahim, Faridah (CMIWS and UiTM Press, 2011)
The September 11th incident has further reinforced the already existing two-value perception between the Western and the Muslim world. Violence, atrocities, uncivilised and cruelties have been equated with the Muslim world. After the incident, Muslims are labelled as terrorists. These ill-conceived and misconstrued meanings of Islam are due to the prejudiced nature of human beings. What is prejudice? A prejudiced mind is inclined to do everything in its power to prevent its world from changing. The prejudiced soul is unwilling to consider any viewpoint other than its own. It is the nature of prejudice that has led many nations engaged in labels and using symbols to associate meanings. Such is the case of the Muslim and the Western societies where prejudiced words are rampantly used to accuse one another. Central to these accusations is the media that used words to impart information and meanings. These meanings are often distorted at the level of reader’s sub-conscious mind. This article tries to explore the nature of prejudice which is manifested in the daily news content particularly war and terrorism news. Issues on the use and misuse of words that are prejudice in nature and have ethical implications on the journalistic practice will also be addressed. In summary, the article will provide insights on alternatives to view the nature of prejudice that are reflected in the use of language, symbols and terms that sometimes dominate most news stories, from the perspectives of general semantics and philosophy of ethics.